(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Iron and Steel Industry is one of the basic industries of the country and plays a crucial role in the development of the sustainable society. Durgapur Steel Plant is one of the integrated steel plants of SAIL and it plays an important role in the industrial development of India. It is in this context after reviewing the literature of the effect of training on employee performance in different sectors it was found that no significant studies are there to ascertain the effectiveness of training in steel sector. This paper carried out a detailed study to find out the impact of different variables on training and development of employees and how to overcome shortcomings in training so that employees can work in effective manner in Durgapur Steel Plant.